The Influence Of E-Service Quality And Product Features Of BSI Mobile Toward Loyalty: Mediation On Customer Satisfaction At Bank Syariah Indonesia Cilegon Branch - Kalyla Fauzia Zahra Darmawan; Ngatno Ngatno; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2026)
Abstract: Bank Syariah Indonesia, a leading Indonesian bank, is leveraging digital banking methods like Internet Banking, Mobile Banking, and SMS Banking to improve customer experiences and loyalty. However, achieving consistent customer satisfaction remains a challenge. A study examining the impact of service quality and product features on loyalty, specifically within the BSI Cilegon branch, revealed that customer satisfaction is not significantly impacted by service quality. However, customer satisfaction positively impacts loyalty, service quality positively impacts loyalty through customer satisfaction, product features impacts loyalty through customer satisfaction. The study recommends BSI to improve service quality by providing accurate customer information and ensuring seamless maintenance to prevent disruptions during transactions.